Pengaruh Pertumbuhan Ekonomi Terhadap Penerimaan Pajak Di Negara-Negera Asean (Periode 2013-2022) - Dita Cahya Kamila; Andryana, Tiara Ayu; Lia Ningrum; Andini Silvia Putri Sudarsono; Nabilah Putri Syahirah (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research aims to determine the influence of economic growth on tax revenues in the countries that are part of ASEAN. This study is a quantitative research that utilizes secondary data obtained from the official websites of the World Bank and CEIC. The research employs correlation analysis to investigate whether economic growth has an impact on tax revenues in the sampled countries, namely Indonesia, Malaysia, Singapore, the Philippines, Vietnam, and Cambodia. The results of the data analysis in this study prove that economic growth does not have an influence on tax revenues in Indonesia, Malaysia, Singapore, the Philippines, Vietnam, and Cambodia.